The long-term effect of Western customs institution on firm innovation in China - Gan Jin; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2024)
Can historical institutions affect today's firm innovation? We analyze a historical experiment in 1902, when the foreign-run Chinese Maritime Customs Service (CMC), known for its efficient and transparent governance, took over some of the notoriously corrupt Chinese Native Custom stations and improved their governance. Using a large data set of contemporary industrial firms in China, we show that firms in locations historically affected by the CMC rules exhibit higher innovation intensities today, which can be attributed to the persisting norms of honesty and lawfulness embedded in the CMC institution. They reduce local corruption and stimulate firms' investment in R&D and training to this day. We identify a causal effect by comparing firms in locations affected by the takeover with firms in similar but unaffected regions nearby. We also use an IV strategy that exploits the takeover criterion, which stipulated that Native Customs stations within a 25 km radius of a CMC customs station could be taken over by the Western powers.
Keywords: N75; N45; D73; Z10; O31; 330; Innovation; Persistence; Institutions; Corruption; China